2007
DOI: 10.1073/pnas.0611653104
|View full text |Cite
|
Sign up to set email alerts
|

Impaired angiogenesis in aminopeptidase N-null mice

Abstract: Aminopeptidase N (APN, CD13; EC 3.4.11.2) is a transmembrane metalloprotease with several functions, depending on the cell type and tissue environment. In tumor vasculature, APN is overexpressed in the endothelium and promotes angiogenesis. However, there have been no reports of in vivo inactivation of the APN gene to validate these findings. Here we evaluated, by targeted disruption of the APN gene, whether APN participates in blood vessel formation and function under normal conditions. Surprisingly, APN-null… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
98
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 42 publications
3
98
0
Order By: Relevance
“…However, the dynamics of their expression pattern is not known. Furthermore, when taking genes outside of the core cluster into account, there are additional vascular enriched genes expressed in both endothelial and mural cells, e.g., CD13 (aminopeptidase N; Rangel et al, 2007), and Gpr124 (Kuhnert et al, 2010). Thus, vascular genes are expressed; (i) in both endothelium and mural cells (Paladin, Gpr124), (ii) predominantly in endothelium (CD31, VE-cadherin) or (iii) preferentially in smooth muscle/pericyte (a-SMA, RGS5).…”
Section: Discussionmentioning
confidence: 99%
“…However, the dynamics of their expression pattern is not known. Furthermore, when taking genes outside of the core cluster into account, there are additional vascular enriched genes expressed in both endothelial and mural cells, e.g., CD13 (aminopeptidase N; Rangel et al, 2007), and Gpr124 (Kuhnert et al, 2010). Thus, vascular genes are expressed; (i) in both endothelium and mural cells (Paladin, Gpr124), (ii) predominantly in endothelium (CD31, VE-cadherin) or (iii) preferentially in smooth muscle/pericyte (a-SMA, RGS5).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by using CD13-null neonatal mice, we demonstrated an impaired angiogenic response in the oxygen-induced retinopathy-of-prematurity model, which quantifies retinal pathological neovascularization in response to hypoxia (22). We have also shown that CD13-null mice displayed dosedependent reduced tumor growth after implantation with either B16-F10 melanoma or Lewis lung carcinoma (LLC) cells, largely because of impaired angiogenesis (12).…”
mentioning
confidence: 93%
“…All of the animal studies were approved through the Institutional Animal Care and Use Committee of the University of Texas M. D. Anderson Cancer Center. CD13 WT and KO BALB/c and C57BL/6 mice were generated as described (12,22). Recipient 8-to 12-wk-old CD13 WT and KO mice were whole body-irradiated in a cobalt irradiator at 12 Gy per mouse (two rounds of radiation at 6 Gy each, with a 2-h recovery interval).…”
Section: Methodsmentioning
confidence: 99%
“…CD13 is a membrane-bound metalloprotease, and is thought to have an important role in chemokine processing and tumour invasion, and therefore is considered an attractive target for inhibiting angiogenesis. Recently, in a CD13-null mice model it was shown that although aminopeptidase-N activity is not essential for embryonic and foetal development, including de novo blood vessel formation (i.e., vasculogenesis) and normal adult function, it is crucial for the pathological development of new blood vessels from existing blood vessels (i.e., angiogenesis) in disease (Rangel et al, 2007).…”
mentioning
confidence: 99%